Extracorporeal Shock Wave Therapy Immediately Affects Achilles Tendon Structure and Widespread Pressure Pain Thresholds in Healthy People: A Repeated-Measures Observational Study. (September 2019) - Leong, Hio Teng; Docking, Sean; Girdwood, Michael; Bonello, Christian; Cook, Jill; Rio, Ebonie
Abstract : Objective: Extracorporeal shockwave therapy is a common clinical treatment for tendinopathy, yet negative effects on tendon structure have been shown in animal studies. This study aimed to investigate the effect of extracorporeal shockwave therapy in healthy participants (i.e., no Achilles tendon pain or pathology). Design: This study examined the effect of three bouts of weekly extracorporeal shockwave therapy for 3 wks in 13 healthy participants. Outcomes measures assessed were as follows: ( a ) Achilles tendon structure, quantified using ultrasound tissue characterization (before and 3 hrs after extracorporeal shockwave therapy), ( b ) pressure pain thresholds, over the Achilles tendon and common extensor tendon origin (before, immediately after, and 3 hrs after extracorporeal shockwave therapy), and ( c ) hop pain (before and immediately after extracorporeal shockwave therapy). Results: There was a significant reduction in echo type I ( P < 0.05) and increase in echo type II ( P < 0.05) at 3 hrs after the first extracorporeal shockwave therapy session that recovered to baseline levels before week 2. There were no significant changes in ultrasound tissue characterization echo pattern observed in subsequent sessions. There were increased pressure pain thresholds immediately after extracorporeal shockwave therapy at the common extensor tendon origin but no significant change at the Achilles tendon. Pressure pain thresholds returned to baseline at 3 hrs after extracorporeal shockwave therapy. There were no significant changes in pressure pain threshold in subsequent sessions. Conclusions: Extracorporeal shockwave therapy resulted in transient changes to tendon structure and widespread hyperalgesia. Abstract : Supplemental digital content is available in the text.